Demographic Characteristics of Food Vendors, Training, Hygiene Practices, Environmental Conditions, Microbiological Quality and Safety of Fast Foods in Cape Coast, Ghana - D. S. Agyirifo (Journal of Applied Sciences and Environmental Management)
Fast foods, including street foods, are essential for tourists and have become increasingly popular in urban areas due to their convenience and affordability compared to home-cooked meals. Consequently, the objective of this paper was to investigate the demographic characteristics of food vendors, their training, hygiene practices, environmental conditions and microbiological quality and safety of fast foods in Cape Coast, Ghana using appropriate standard techniques by collecting food samples such as fried rice, fried chicken, coleslaw, and pepper sauce (Shito), from seven areas within the Cape Coast municipality and analyzed for microbial load and temperature. The study revealed a high prevalence of foodborne pathogens. Most of the food vendors obtained training either through a vocational institute (29.2 %) or apprenticeship (41.7%) and 75% of them had medical examination once a year. The highest temperature for a packed meal was 78.5 oC while the least was 23.3 oC. Coleslaw had the highest coliform count (49.5 x 107 cfu/g) and Salmonella sp count (20.1 x103 cfu/g). The fried chicken had the least count. Aspergillus sp was the most isolated from the packed meal. Despite 91.7% of vendors being licensed and most having some knowledge of food hygiene practices, the findings emphasize food safety and hygiene practices inadequacies among street food vendors. This study contributes to the broader understanding of food safety challenges in developing urban settings and the need for improved regulatory frameworks to safeguard local consumers and tourists.